1992
DOI: 10.1212/wnl.42.6.1214
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic HIV infection does not cause EEG abnormalities

Abstract: We conducted EEG testing in 200 asymptomatic homosexual men, half of whom were HIV seropositive. We chose to include half of the subjects because they were rated as impaired on a neuropsychological screening test. We used both traditional visual EEG interpretation and quantitative EEG analysis. Abnormal EEGs and borderline degrees of EEG slowing occurred in 32% of these men. These EEG changes were not related to HIV serostatus. EEG changes did correlate with the impaired neuropsychological test performance. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…EEG changes are uncommon and mild in alcoholic dementia unless it is combined with hepatic encephalopa thy [103,104], EEG is usually normal in neuro-psvchologically unimpaired patients infected with / / / f ' [ 105] AIDS and AIDS-related complex, the incidence and sever ity of abnormal EEG increases with the development of AIDS-related dementia with diffuse and/or focal slowing and in 10% focal epileptiform activity [106]. In normal pressure hydrocephalus the EEG shows a diffuse slowing which is correlated with the CSF outflow resistance.…”
Section: Eeg In Dementia Of V Arious Aetiologiesmentioning
confidence: 99%
“…EEG changes are uncommon and mild in alcoholic dementia unless it is combined with hepatic encephalopa thy [103,104], EEG is usually normal in neuro-psvchologically unimpaired patients infected with / / / f ' [ 105] AIDS and AIDS-related complex, the incidence and sever ity of abnormal EEG increases with the development of AIDS-related dementia with diffuse and/or focal slowing and in 10% focal epileptiform activity [106]. In normal pressure hydrocephalus the EEG shows a diffuse slowing which is correlated with the CSF outflow resistance.…”
Section: Eeg In Dementia Of V Arious Aetiologiesmentioning
confidence: 99%
“…Other abnormalities included a lower maximal amplitude of dominant background activity and more marked generalized and anterior disturbances on EEG in early HIV-1 infection compared with uninfected controls (99). However, in a series from the multicenter AIDS cohort study, no EEG abnormalities could be attributed to HIV-1 infection in otherwise asymptomatic individuals (274). Computerized spectral analysis of the EEG has also been used in this regard (173,281,282) and may be more sensitive than routine EEG (282).…”
Section: Neuropsychological Testsmentioning
confidence: 99%
“…The MACS study13 has reported no difference in the incidence of EEG abnormalities in asymptomatic subjects when compared with seronegative controls, but Parisi et al 14 reported that EEG abnormality might be a predictor of CNS involvement.…”
mentioning
confidence: 98%